Congenital melanocytic nevi management: question - Stefania Guida; Giacomo Giovanni Urtis; Giuseppe Rubino; Giovanni Pellacani; Francesca Farnetani (Hygeia Press di Corridori Marinella, 2016)
A 12-year-old girl presented to our attention for a pigmented lesion having greatest diameter of 2.5 cm, located on her left forehead, involving the ipsilateral eyebrow. This lesion had appeared as a flat brown macule at birth. With passing years, the lesion showed an increased diameter and thickness and it became progressively darker. 1. What reasons can justify the excision of congenital melanocytic nevi? 2. Which treatment do you think would be more appropriate? 3. Is there a right age to remove a congenital melanocytic nevus?